Conceptual strategy for pelvic resections in tumor patients - Vyrva, Oleg; Malyk, Roman; Golovina, Yanina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Pelvic resection is a technique that involves surgical resection of portions of the pelvic girdle. Hemipelvectomy is a pelvic resection that salvages an ipsilateral limb. The main indication for these procedures is primary malignant tumors of the pelvis (mostly chondrosarcomas), but in rare cases they are indicated for metastatic lesions, infection, or trauma. Objective: the main purpose of this study was to analyze pelvic resection patients. Methods: the results of treatment of 239 patients (131 male and 108 female) with pelvic tumors who were undergoing surgeries procedures in the Sytenko Institute from 1963 till 2017 were evalueted. 186 patients were operated at modern era in 2004–2017. The most frequent nosologies were chondrosarcomas, osteochondromas and secondary metastatic lesions. The average age of patients was (37.2 ± 18.9) years (7–80). Preoperative planning is crucial to define the extent of the tumor, plan the surgical margins, and identify the location of the vital structures. Necessary imaging includes plain radiography, CT, and MRI. There were 38 patients with type I resection (by Enneking and Dunham classification), 132 — with II type and 69 — with III type resection in our series. Results: reconstruction is dictated by the extent of the resection and the remaining structures. Surgical technique is dictated by histology of the tumor and location of the lesion. Allograft and autograft pelvic reconstruction has been used for patients. The TESS and MSTS have been applied to assess function outcomes. Wound infection and flap necrosis, nonunion, nerve palsy and local recurrence of malignant tumors are the most common complications for hemipelvectomies and pelvic resections. Conclusions: a multidisciplinary team is required for treat bone tumor of a pelvis. Appropriate preoperative counseling with the patient and family is paramount to explain the magnitude of the procedure, common complications, and predicted functional loss.